(untitled) - Bailey, Richard E. (Boston, 2004)
This process-oriented, paragraph-to-essay level workbook teaches students to write well by drawing on the ways in which they already use language effectively - in thinking, speaking, writing informally, and reading. The text's integrated approach to grammar and its emphasis on writing's real-life applications set it apart from its competitors.
Keywords: English language,English language,Report writing,Tiếng Anh,Tiếng Anh,Viết báo cáo; Paragraphs,Problems, exercise, etc,Rhetoric,Problems, exercise, etc,Problems, exercise, etc,Đoạn văn,Bài tập, Các vấn đề, vv.,Tu từ học,Bài tập, Các vấn đề, vv.,Bài tập, Các vấn đề, vv